Optimalisasi Pemanfaatan Media Laboratorium Virtual dan Alat Percobaan IPA Berbasis Lingkungan Untuk Meningkatkan Kompetensi Guru Sekolah Dasar - Triwiyono, Triwiyono; Boy, Bonefasius Y.; Inggamer, Mamberuman M. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Several obstacles in learning experienced by SD Negeri Inpres Perumnas I Waena teachers, Jayapura City include (1) inadequate Natural Sciences learning facilities available, (2) teachers' mastery of information technology is still lacking, and (3) teachers' skills in designing and making experiment tools/ props are still low. This community service aims to: (1) improve teachers' skills in using virtual laboratories, (2) improve teachers' skills in designing and making science experimental tools from materials taken from the home/school environment, and (3) increasing teacher competence. The method used is training in the form of practical work using virtual laboratory media, designing and making environment-based science experimental tools. Training materials according to teacher needs: (1) utilization of virtual laboratory media, and (2) manufacture of science experiment tools. The location of the activity was at Perumnas I Waena Public Elementary School, Jayapura City, with 31 teachers participating in the activity and implementation time in July 2022. The results of the activity showed that: (1) there was an increase in the skills of the activity participants in using the virtual laboratory, (2) there was an increase in the skills of the activity participants in designing and manufacturing environment-based science experimental tools, and (3) the activity participants increased their competence.